Pengaruh Disiplin Kerja, Komunikasi, dan Kejelasan Peran terhadap Kinerja Karyawan dengan Dukungan Sosial sebagai Variabel Moderator di PT. XYZ Construction Surabaya - Riska Carollina; Tri Andjarwati; M. Sihab Ridwan (Journal of Economics, Management, and Accounting, 2025)
This study was conducted to examine the influence of work discipline, communication, and role clarity on employee performance and to analyze the moderating role of social support within the organizational context of PT. XYZ Construction Surabaya. The research was motivated by the recurring issues of declining performance and project delays, which indicated inadequate work discipline, ineffective communication flows, and role ambiguity among employees. Existing studies had not yet comprehensively integrated these variables in a single empirical model nor evaluated the moderating effect of social support in the construction industry setting, creating a research gap that this study intended to address. A quantitative research method was applied, involving 90 employees selected through a saturated sampling technique, and the data were analyzed using Structural Equation Modeling with Partial Least Squares. The findings showed that work discipline, communication, and role clarity positively and significantly affected employee performance, while social support did not moderate these relationships. The model explained 48.0% of the variance in Employee Performance (R2=0.480). The study contributed theoretically by confirming the dominant role of structural performance drivers over psychosocial support, and practically by providing managerial insights into improving performance in project-based environments. Suggestions for future research were provided based on identified limitations.